Evidence-based cybersecurity : foundations, research, and practice - Pomerleau, Pierre-Luc; Maimon, David (Security, audit and leadership, 2022)
"The prevalence of cyber-dependent crimes and illegal activities that can only be performed using a computer, computer networks, or other forms of information communication technology has significantly increased during the last two decades in the USA and worldwide. As a result, cybersecurity scholars and practitioners have developed various tools and policies to reduce individuals' and organizations' risk of experiencing cyber-dependent crimes. However, although cybersecurity research and tools production efforts have increased substantially, very little attention has been devoted to identifying potential comprehensive interventions that consider both human and technical aspects of the local ecology within which these crimes emerge and persist. Moreover, it appears that rigorous scientific assessments of these technologies and policies "in the wild" have been dismissed during the process of encouraging innovation and marketing. -- Consequently, governmental organizations, public and private companies allocate a considerable portion of their operations budgets to protecting their computer and internet infrastructures without understanding the effectiveness of various tools and policies in reducing the myriad of risks they face. Unfortunately, this practice may complicate organizational workflows and increase costs for government entities, businesses, and consumers. The success of the evidence-based approach in improving the performances of a wide range of professions (for example, medicine, policing, and education) leads us to believe that an evidence-based cybersecurity approach is critical for improving cybersecurity efforts.
Keywords: Computer security; Comptuter networks : Security measures; Computer crimes : Prevention; tietoverkot; kyberturvallisuus; tietoturva; tietotekniikkarikokset; ennaltaehkäisy